Students’ Perceptions and Financial Challenges in the Absence of Local Higher Education Institutions: Evidence from a Rural Philippine Municipality - Kenneth Panga; Princess Sarah P. Estrada (MASI Mandiri Edukasi, 2026)
This study examines the academic and financial implications of not having a local Higher Education Institution (HEI) in the Municipality of Ocampo, Camarines Sur, Philippines. Using a descriptive–correlational design, data were gathered through a structured survey from 63 students enrolled in tertiary institutions outside the municipality. Findings indicate that most respondents perceived the lack of a nearby HEI as influencing their academic choices, limiting access to educational opportunities, and increasing emotional and logistical challenges. Students also reported considerable financial burdens, including transportation, food, accommodation, and other education-related expenses. Spearman's rank correlation analysis revealed a statistically significant relationship between students’ negative perceptions and their financial difficulties (p = 0.01632, n = 63), indicating that greater perceived disadvantage is associated with higher financial strain. These results highlight the intersection of geographic and economic barriers that constrain rural students’ participation in higher education and underscore the need for localized higher education initiatives and targeted financial support programs to promote equitable access.